THE IMPORTANCE OF THE PRESENCE OF THE PRINCIPAL OR PLAINTIFF IN THE EVIDENCE PROCESS OF CIVIL PROCEDURAL LAW - syailendra, Moody Rizqy; Manggal, Adam Tanzio (Jurnal Indonesia Sosial Sains, 2025)
The civil court process is certainly different from other types of courts, such as criminal, administrative, military, and international courts. Civil courts are quite unique and complex, with judges tending to be passive, placing the burden of proof on the parties involved in the case. The agenda for hearing witness testimony is a crucial aspect of this process, and it is essential that both parties—the plaintiff and the defendant—respect and adhere to the applicable civil court procedures, such as those outlined in the HIR (High Court Regulations) applicable in Java and Madura, and the Rbg (Regional Court Regulations) applicable outside Java and Madura. This article aims to emphasize that the parties involved in the case should not arbitrarily withdraw their claims or unilaterally refuse to attend the scheduled hearing agenda, to prevent any abuse of power between one party and another, where one party prioritizes their own rights without considering the dignity of the court or the rights of others.